1984
DOI: 10.1302/0301-620x.66b2.6707057
|View full text |Cite
|
Sign up to set email alerts
|

Telescoping osteotomy for pressure metatarsalgia

Abstract: A review is presented of 508 feet in 310 patients after telescoping osteotomy of the lesser metatarsals for metatarsalgia. The patients were predominantly female (80%), with a mean age of 55 years; the range of follow-up was 1 to 12 years. In 22% of the patients the metatarsalgia was associated with rheumatoid arthritis. Improvements in assessment and modifications in technique are reported and the management of complications is discussed. The results show that telescoping osteotomy for established cases of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 2 publications
1
47
0
2
Order By: Relevance
“…Preoperatively 23 of 32 MTP joints were diagnosed as dislocated and correction was obtained in 5 of 32 at follow-up. Helal and Greiss (1984) noted successful reduction of pain in 88%, but this has not been con rmed by others. Winson et al (1988) obtained good pain reduction in 47%, and Mulier et al (1994) had good results in only 50%.…”
Section: Complicationsmentioning
confidence: 84%
See 2 more Smart Citations
“…Preoperatively 23 of 32 MTP joints were diagnosed as dislocated and correction was obtained in 5 of 32 at follow-up. Helal and Greiss (1984) noted successful reduction of pain in 88%, but this has not been con rmed by others. Winson et al (1988) obtained good pain reduction in 47%, and Mulier et al (1994) had good results in only 50%.…”
Section: Complicationsmentioning
confidence: 84%
“…Two of the screws and all migrated K-wires had to be removed. Helal and Greiss (1984) suggested that shortening of the metatarsal without touching the joint capsules would allow passive correction of the subluxation or dislocation. Mulier et al (1994) and Winson et al (1988) found that this is not correct.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Der rheumatische Vorfuß ist ein in der Literatur häufig behandeltes Problem (3)(4)(5)(6)(7)(14)(15)(16). Infekte in diesem Bereich sind sehr ernst zu nehmen, da sie auf umgebende Weichteil-und Knochenareale über-greifen können.…”
Section: Diskussionunclassified
“…Surgical repair of plantar plate ligament disruption has evolved with increasing appreciation of the anatomy of the MTPJ (7,8). Primary repairs that involve direct visualization of the plantar plate injury through dorsal and plantar incisional approaches have been described (9)(10)(11)(12), and procedures aimed at restoring MTPJ stability have been reported with the use of anchors (10), extensor tendon lengthening (13,14), flexor tendon transfers (14)(15)(16)(17), crossover second toe repair (14,16), metatarsal osteotomy (11,18,19), and total joint implantation (20). However, considerable controversy still exists regarding the optimal operative intervention for this pathologic entity (12,17).…”
mentioning
confidence: 99%